STEPWISE HYDROGEN REMOVAL IN THE ENZYMATIC RING EXPANSION OF PENICILLIN-N TO DEACETOXYCEPHALOSPORIN-C - Baldwin, J; Adlington, R; Aplin, R; Crouch, N; Schofield, C; Ting, H (1987)
Reaction of a 1:1 mixture of penicillin N and 2,2-bis(trideuteriomethyl) penicillin N with partially purified deacetoxy-cephalosporin C/deacetylcephalosporin C synthetase from Cephalosporium acremonium CO 728 resulted in preferential conversion of the protiated substrate, whereas in similar experiments with a 1:1 mixture of penicillin N and 3-deuteriopenicillin N both substrates were converted at the same rate; these results accord with a stepwise process for hydrogen removal during the ring expansion in which the methyl hydrogen is first removed.